Enhancement of the energy storage properties of supercapacitors using graphene nanosheets dispersed with macro-structured porous copper oxide. (1st May 2015) - Dar, Riyaz A.; Naikoo, Gowhar A.; Kalambate, Pramod K.; Giri, Lily; Khan, Farid; Karna, Shashi P.; Srivastava, Ashwini K.
Graphical abstract: Highlights: Synthesis of macro structured porous CuO monoliths via modified Sol–Gel route. Fabrication of graphene/macroCuO composite electrodes. Macro structured porous CuO shows pseudocapacitive behaviour. The composite exhibits a high specific capacitance of 455 F g −1 at 0.125 A g −1 . Graphene/macroCuO composite electrode results good cycling performance. Abstract: Graphene nanosheets (GN) dispersed with macroporous copper oxide (macroCuO) was investigated as an electrode material for supercapacitors. A facile and cost-effective synthesis approach was used to prepare macro-structured porous copper oxide monoliths via modified Sol–Gel route. 1, 3, 5-trimethylbenzene was used as an organic structural directing agent to enhance the pore size, pore volume, pore density and surface area of the resulting CuO hybrid templated with Pluronic P-123. GN/macroCuO nanocomposite was prepared by ultrasonication of the GN and macroCuO. The macroCuO and GN/macroCuO nanocomposite were characterized using various surface analytical techniques. Electrochemical performance of the composite electrode was investigated using cyclic voltammetry and chronopotentiometry. GN/macroCuO/GCE showed pseudocapacitance behaviour due to the Faradaic type of capacitance involving redox process between Cu (0) and Cu (II) of porous copper oxide network. Electrochemical measurements revealed the maximum specific capacitance, energy density and power density of 417 F g −1, 58 Wh kg −1 and 17.85 kW kg −1, respectively for the supercapacitor based on GN/ macroCuO nanocomposite electrode at a current density of 0.9 A g −1 . The fabricated supercapacitor device exhibited excellent cycle life with 91.4% of the initial specific capacitance retained after 1000 cycles. The results suggest that the hybrid composite is a promising supercapacitor electrode material.